Digital Media Hospital: Aplikasi Komunikasi Pemasaran Berbasiskan Daring - Rony, Noor Firmansyah; Panuju, Redi (Jurnal Komunikasi Profesional, 2018)
The research aims to explain how digital media in RSPHC CARE application can be applied to marketing communication using 4P (Jerome Mc.Carthy) and 4C (Lauterborn) concept, and explain how marketing communication through digital media in RSPHC CARE application attracts people as consumers to use health services in PHC Surabaya hospital. The research used in-depth interviews, observations, and documentation focusing on data discovery. The subject of research is the manager of digital media in RSPHC CARE application and customers. The object of this research is marketing communication through digital media in RSPHC CARE application in information delivery and promoting hospital service of PHC Surabaya. The result is PHC Surabaya hospital, in addition to using digital media in RSPHC CARE application as online registration media to fulfill customer requirement, also utilize as marketing communication media on some features in it to inform things covering product (service) price, place, and promotion (4P). And can be maximized to use some of its features by committing to customers (4C). Some features in digital media in RSPHC CARE’s application at PHC Surabaya hospital support marketing communication activities, based on 4C and 4P concepts in marketing communications. Keywords:Digital Media, Hospital, Marketing Communications, 4P - 4C Concepts in Marketing Communications.